2018
DOI: 10.20517/2394-5079.2017.46
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular sub-classification of hepatocellular carcinoma relative to alpha-fetoprotein level in an Asia-Pacific island cohort

Abstract: AimIncreased serum alpha-fetoprotein (AFP) levels are associated with specific molecular sub-classes of hepatocellular carcinoma (HCC), supporting AFP as a predictive or therapeutic biomarker for precision treatment of this disease. Considering recent efforts to validate HCC molecular classification systems across different populations, we applied existing signature-based classification templates to Hawaii cohorts and examined whether associations between HCC molecular sub-class, AFP levels, and clinical featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…AFP performance in this study was within the ranges reported in the literature [62]. It is commonly reported for AFP to have low sensitivity in early stage HCC as AFP is only secreted by certain molecular subtypes of HCC [63], and in those which do, AFP levels positively correlate with tumor size, number, differentiation and vascular invasion [7]. Sensitivity of AFP was low when compared to the TA-AAb panel for stage one HCCs (17% vs 29%) but improved for later stages.…”
Section: Plos Onesupporting
confidence: 83%
“…AFP performance in this study was within the ranges reported in the literature [62]. It is commonly reported for AFP to have low sensitivity in early stage HCC as AFP is only secreted by certain molecular subtypes of HCC [63], and in those which do, AFP levels positively correlate with tumor size, number, differentiation and vascular invasion [7]. Sensitivity of AFP was low when compared to the TA-AAb panel for stage one HCCs (17% vs 29%) but improved for later stages.…”
Section: Plos Onesupporting
confidence: 83%
“…Importantly, a high AFP expression (>400 ng/mL) is a recognized manifestation of HCC with aggressive biological behavior, and it can also serve as a reflection of tumor burden. 48 , 49 In the present study, clinical characteristics of a specific patient population with HCC with preoperative high AFP levels after curative liver resection were depicted, and their long-term oncologic prognosis and prognostic factors were evaluated. Using the magnitude in decline between preoperative and postoperative serum AFP levels, ie whether a postoperative biomarker response could completely be achieved at the first postoperative follow-up or not, the whole cohort (n=549 patients) was divided into the CBR group (n=456) and the IBR group (n=93).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, S3 tumors were smaller, well-differentiated, and overexpressing genes related to liver function (e.g., glycolipid metabolism related genes). With regard to prognosis, up-regulated AFP was associated with aggressive tumor and poor clinical outcome [69]. The S2 subtype was also associated with poor prognosis.…”
Section: Transcriptomic Hcc Subtypingmentioning
confidence: 97%